Measurement of the Traffic Wheel/Pavement Contact Characteristics for Goods Haulage; Case Study of Dangote Flour Mill PLC Ilorin, Nigeria. Issue 1 (1st January 2020) - Oguntayo, Daniel Oluwafemi; Adelowo, Idris Taiye; Olaleye, Joseph Kunle
Abstract: In Nigeria, goods haulage is currently dominated through heavy trucks, whose effect on the pavement deterioration can be enormous, because the truck wheel/pavement interaction plays a key role in deterioration of pavement life. This study aims to measure the truck wheel/pavement contact characteristics with a view to develop its quantitative damaging influence on a pavement structure. Axle load distribution, tyre inflation pressure and tyre/pavement contact area of selected tyre types for different axle configurations were determined for four classes of trucks being used by a major haulage outfit in Nigeria, Messrs Dangote Industries Limited. The results obtained showed that the tyre pavement contact length depends on tyre load as the length increases with increase in tyre load, while tyre pavement contact width is averagely constant with tyre load increase. It is concluded that design and use of tyres should allow for large contact areas with small tyre pressures to lessen the menace of pavement deterioration, and also there is need for a strict control for standards of truck loads that travel on Nigerian road.